Hil dig, Frelser og Forsoner!, et nærlæsningsforsøg - Michelsen, William (Grundtvig-Studier, 1972)
Hil dig, Frelser og Forsoner. An essay in close reading By William Michelsen This article should be read as a reply to Niels Egebaks interpretation of the same hymn in Grundtvig-Studier 1971. Jørgen Elbek3s characterisation of Grundtvig’s Sang-Værk - the point that it “demands to be regarded as the unanimous hymn of praise of the Danish church of today” (ibid. 1959) - and Magnus Stevns’s analysis of the difference between Grundtvig’s and Kingo’s Easter hymns are adduced in support of the claim that from beginning to end this hymn aims at the paradoxical goal of loving life while bearing in mind the reality of death. It is only in the beginning of the poem, however, that this aim is enigmatic, where the image of winding a rose garland round the Cross is employed. - Egebak seems to regard the religious feelings expressed in Grundtvig’s hymns as an ideology created by the human mind, that is, something that man can trace back to himself. Instead, the claim is made that faith is confidence in something beyond man. Man cannot live without a greater or lesser amount of confidence in his environment. Confidence in an extra-human outside world is a condition for existence, which manifests itself in religion or religious feelings. The Gospel of Christ presupposes this situation. So does the hymn we are concerned with. The writer of a poem is speaking for himself, but the hymn writer is speaking on behalf of any Christian. In this point lies the difference in kind between the poem “De Levendes Land” and the hymn “O Christelighed!” - A hymn presupposes faith. A poem may lead towards faith or away from faith or be indifferent towards faith. A poem may express nihilism, a hymn may not. – An ideology or theology may be a conceptual superstructure on the fundamental faith. But neither ideology nor theology is faith. It is inconceivable that the word “ troer” in st. 2 should express a mere assumption, let alone st. 8 and st. 11. The reason that the Danish Hymn Book leaves out st.2-4 may be certain offending expressions, or that they express a belief that is not common to all worshippers (“Thi jeg troer, Du er tilstæde” ). Here, then, we have an aspect of faith that is disputed, but not an assumption. Egebak identifies the “ I” of the hymn with “the writer” rather than with the individual Christian singing the hymn, and he confronts the two persons with each other. This confrontation is at odds with the concept of “hymn” as a literary genre. But it is particularly unreasonable when, as here, we are dealing with a new version of an old hymn. Egebak’s opposition between “ the world” and “ I” (of st. 1) as if it covertly pervaded the whole hymn presupposes a pietistic line of thought that is alien to the hymn. I cannot change “Hjertets Haardhed, Hjertets Kulde” – only God can. Egebak is right that death is the personal cause of the despair and doubts of human being - and this is true not only in the case of the hymn writer. Faith is an answer to this, but to man it remains an insoluble mystery. The poet cannot redeem himself; but a hymn is the literary expression of faith, frequently wavering, in a superhuman power.